2018
DOI: 10.1016/j.ijvsm.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Newcastle disease virus in backyard chickens and herd-level risk factors of Newcastle disease in poultry farms in Oman

Abstract: Newcastle disease (ND) is an endemic disease in Oman’s poultry industry and impacts negatively on food security. However, little is known regarding the potential risks of the disease in backyard poultry. The objectives of this study were to determine the seroprevalence of Newcastle disease virus (NDV) in backyard chickens and the herd-level risk factors in Oman. In total, 1383 serum samples were collected from chickens in 139 flocks from nine governorates. Information on associated risk factors was assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
2
17
3
Order By: Relevance
“…ND is regarded as an enzootic disease in Oman [16], [17]. The findings herein with reports of vNDV presence in vaccinated birds could imply increasing replication of the virus, thus precipitating high environmental viral load.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…ND is regarded as an enzootic disease in Oman [16], [17]. The findings herein with reports of vNDV presence in vaccinated birds could imply increasing replication of the virus, thus precipitating high environmental viral load.…”
Section: Discussionsupporting
confidence: 75%
“…This is more important with the growing need for the evaluation of the efficacy of existing ND vaccines [5]. In Oman, ND has been identified as a major cause of setbacks in the poultry industry [16], [17]. In this study, we were able to isolate and characterize the NDV responsible for the outbreaks recorded in three large commercial flocks in Oman.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, we took paired samples; the first sample was taken at the beginning of the disease, while the second sample was taken 2-3 weeks later. In fact, since the concentration of antibodies increases between the two sera collected, this indicates that we had stimulation of the immune system that could be due to a recent infection or to symptomatic viral reactivation [9-11,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Alsahami et al . [9] and Bulbule et al . [33] reported that the NDV vaccine of different strains was being used to control clinical disease during the outbreak.…”
Section: Discussionmentioning
confidence: 99%